The Synergism of the Small Molecule ENOblock and Fluconazole Against Fluconazole-Resistant Candida albicans - Li, Liping; Zhang, Teng; Xu, Jianrong; Wu, Jing; Wang, Yida; Qiu, Xiran; Zhang, Yu; Hou, Weitong; Yan, Lan; An, Maomao; Jiang, Yuanying (Frontiers in Microbiology, 2019)
Candida albicans is the most common opportunistic fungal pathogen which can cause life-threatening bloodstream infections known as candidaemia. It is very important to discover new drugs and targets for the treatment of candidaemia. In this study, we first investigated the combination antifungal effects of the small molecule ENOblock and fluconazole (FLC) against FLC-resistant C. albicans. A checkerboard microdilution assay showed that ENOblock has a significant synergistic effect in combination with FLC against FLC-resistant C. albicans. The time-kill curve further confirmed the synergism of this compound with FLC against FLC-resistant C. albicans. Moreover, we demonstrated the significant inhibitory effects of ENOblock alone and in combination with FLC against C. albicans hypha and biofilm formation. Furthermore, the XTT assay showed that ENOblock has relatively low toxicity to human umbilical vein endothelial cells. The in vivo antifungal efficacy of ENOblock was further assessed in a murine model of systemic C. albicans infection. Although ENOblock alone was not sufficient to treat C. albicans infection, the combination of FLC and ENOblock showed significant in vivo activity against FLC-resistant C. albicans. Finally, using surface plasmon resonance analysis as well as an inhibition assay, we determined that ENOblock directly interacted with CaEno1 and significantly inhibited the transglutaminase activity of this enzyme, which is involved in the growth and morphogenesis of C. albicans. In summary, these results demonstrate the synergistic effects of FLC and ENOblock against FLC-resistant C. albicans, and indicate that inhibition of the transglutaminase activity of CaEno1 by ENOblock might confer an advantage for the synergism of FLC and ENOblock, suggesting the potential of ENOblock as a new antifungal candidate.